The Association Between Force-Velocity Relationship in Countermovement Jump and Sprint With Approach Jump, Linear Acceleration and Change of Direction Ability in Volleyball Players - Pleša, Jernej; Kozinc, Žiga; Šarabon, Nejc (Frontiers in Physiology, 2021)
The force-velocity (FV) relationship allows the identification of the mechanical capabilities of musculoskeletal system to produce force, power and velocity. The aim of this study was to assess the associations of the mechanical variables derived from the force-velocity (FV) relationship with approach jump, linear sprint and change of direction (CoD) ability in young male volleyball players. Thirty-seven participants performed countermovement jumps with incremental loads from bodyweight to 50-100 kg (depending on the individual capabilities), 25-meter sprint with split times being recorded for the purpose of FV relationship calculation, two CoD tests (505 test and modified T-test) and approach jump. Results in this study show that approach jump performance seems to be influenced by maximal power output (r = 0.53) and horizontal force production (r = 0.51) in sprinting, as well as force capacity in jumping (r = 0.45). Only the FV variables obtained from sprinting alone contributed to explaining linear sprinting and CoD ability (r = 0.35-0.93). An interesting finding is that sprinting FV variables have similar and some even stronger correlation with approach jump performance than jumping FV variables, which needs to be considered for volleyball training optimization. Based on the results of this study it seems that parameters that refer to horizontal movement capacity are important for volleyball athletic performance. Further interventional studies are needed to check how to implement specific FV-profile-based training programs to improve specific mechanical capabilities that determine volleyball athletic performance and influence the specific physical performance of volleyball players.